Yaba-like disease virus protein 7L is a cell-surface receptor for chemokine CCL1 - Najarro, Pilar; Lee, Han-Joo; Fox, James; Pease, James; Smith, Geoffrey L. (Journal of General Virology, 2003)
Yaba-like disease virus (YLDV) genes 7L and 145R are located on opposite ends of the genome and are predicted to encode 7-transmembrane proteins (7-TM) that share 53 and 44 % amino acid identity, respectively, to human CC chemokine receptor 8 (hCCR8). In this report, we demonstrate that early after infection with YLDV, cells acquire the ability to bind human CCL1. By expression of genes 7L and 145R in vaccinia virus, we demonstrated that each protein is glycosylated and is exposed on the cell surface with the N terminus outside the cell. Protein 7L, but not 145R, is able to bind hCCL1 (K d=0·6±0·13 nM) and couple to heterotrimeric G-proteins and to activate the extracellular signal-regulated kinases (ERK1/2). 7L binds several chemokines including the viral chemokines vMIPI and vMIPII and hCCL7/MCP3. This binding seems species-specific as 7L does not bind the murine orthologues of CCL1 and CCL7 in the assays used. This represents the first example of a poxviral 7-TM chemokine receptor that has functional interactions with a human chemokine.